CFD simulations of inhalation through a subject-specific human larynx – Impact of the unilateral vocal fold immobility - Voss, Samuel; Vutlapalli, Swetha Chowdary; Saalfeld, Patrick; Arens, Christoph; Janiga, Gabor (Computers in biology and medicine, 2022)
The larynx of the human respiratory tract plays a vital role in breathing and voice production. Both can be influenced by functional and/or morphological changes of the larynx, e.g., immobility of one or both vocal folds (VF). The immobile VF can become stationary in different positions such as the median, paramedian, intermediate or lateral position. The impact of unilateral vocal fold immobility (UVFI) on inhalation is the focus of this study. Transient numerical simulations of the inhalation process in patient-specific airways are performed. Five configurations are considered: paramedian and intermediate VF positions on the left and right, and healthy. Large eddy simulations are used to describe the complex laryngeal turbulent flow. Airway resistance, power loss, and spectral entropy are calculated to quantify the work of inspiration and evaluate flow regimes. The laryngeal jet intensity and flow disturbance increase with the severity of immobility. In comparison to the healthy configuration, UVFI with right/left intermediate and right/left paramedian VF position increases the airway resistance over the oropharynx to the trachea by 69%/58% and 310%/285%, respectively. When the entire respiratory system is considered, an increase of up to 48% is estimated. Spectral entropy increases of up to 2.5 times indicate higher turbulence levels due to UVFI. Surgery of immobile VF aims to improve glottis closure. However, this can have a negative impact on breathing efficiency. To that end, this study provides initial insights into the conflicting objectives of open versus closed VFs. •LES simulations of subject-specific UVFI configurations•Analysis of laryngeal jet generation and jet travelling length•Quantification of flow transition with spectral entropy•Increased airway resistance and power loss with higher airway constriction due to UVFI